Physical rehabilitation of hearing-impaired athletes after musculoskeletal injuries - Seselkin, A. I.; Kartashev, V. P.; Karpova, N. V.; Chernetskaia, K. A, (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of a new physical rehabilitation method for the hearing-impaired athletes after musculoskeletal injuries, with the radial head fracture taken for the case study to analyze benefits of the immobilizing, post-immobilizing and rehabilitation process stages with application of exercise therapy, massage, yoga and water rehabilitation methods. For the purposes of the study we applied the Mironov-Burmakova`s test to rate pain in the elbow joint; the same test adapted by V.A. Kalantyrskaya to rate amplitudes of the flexion-extension and rotation movements in the elbow joint; hand-held dynamometry; bodily functional status rating tests; educational experiment; and standard mathematical methods of statistics; with the muscular strength rated by the hand-held dynamometry. Subject to the experiment and tests were 15 hearing-impaired sambo and judo wrestlers; diagnosed with radial head fracture; and split up into Experimental and Reference Groups (EG, RG). The physical rehabilitation model was found beneficial as verified by the significant progress of the EG versus RG in muscle strength, joint flexion and rotation rating tests.